TANTANGAN KEPEMIMPINAN MANAJERIAL ORGANISASI PERGURUAN TINGGI, PREDIKTOR EFISIENSI MANAJEMEN SISTEM PENDIDIKAN NASIONAL - Alex Rumondor (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractIn accordance to the Republic of Indonesia Law of National Education System which isknown as â€œSisdiknasâ€(Sistem Pendidikan Nasional) Law Number 20, Year 2001, thenational education system in Indonesia should guarantee the universities managementefficiency. Besides other factor of universitiesâ€™ capability to implement the autonomy ofuniversities organizational management; either in academic, personal, financial fields or inother functional areas regulated by each university. Following the government regulationLaw Number 99 Year 2001 concerning the Education National Standard, normatively infact that law is challenging the universities organizational management locally, nationallyand globally and today this become the object of study of the organizational communication.Our contemporary understanding actually has accepted that leadership is basicallyinfluence the daily interpersonal communication in the life of organization even itdetermines the achievement of organizationâ€™s objectives. No motivation found amonguniversitiesâ€™ leaders is often caused of dissension in the managing leadership of theorganization.Keywords: Managing Leadership, Universities Organization, National Education System.